Taxonomy of Coelogyne section Fuliginosae (Orchidaceae): new species, notes, resurrections and typifications - Adit, Arjun; Kumar, Pankaj (Phytotaxa, 2024)
Coelogyne tripurensis is described here as a species new to science. This epiphytic orchid was discovered from the moist broadleaf forests of Jampui Hills in Tripura, North-East India situated at the westernmost fringe of Indo-Myanmar Biodiversity Hotspot. Evidences to delineate the newly described species and its significant differences from closely related taxa have been provided. We discuss the resurrection of C. fuliginosa, C. leungiana and C. pallens as distinct species. Additionally, lectotypification of C. chrysotropis, C. ovalis and C. pallens, and neotypification of C. fuliginosa is presented. We also provide historical evidence for the range extension of C. phitamii in Thailand. An identification key for the taxonomically challenging Coelogyne section Fuliginosae which consists of nine species is provided along with detailed nomenclatural notes on each species as a revision of the section.